Comparison of awareness, attitude and use of non-prescription drugs among medical and non-medical undergraduates: a questionnaire based study - Tikoo, Deepika; Gupta, Meenakshi; Sharma, Geeta (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The use of non-prescription drugs for self-treatment of common ailments is becoming increasingly popular in our society. Trends in the use of non-prescription drugs is expected to vary among medical students and the general population, as medical students have more knowledge about drugs and an easy access to them. In the present study we have done a comparison regarding the awareness, attitudes and use of over the counter drugs among medical and non-medical undergraduates to evaluate these parameters. Methods: A total of 139 third year medical students and 101 non-medical students were included in our study. An anonymous, pre-validated questionnaires containing questions about their knowledge, attitude and perception of non-prescription drugs were filled by them. The data collected was compiled and analyzed by frequency analysis and percentages. Results: Majority of the medical (99.3%) and non-medical students (95.1%) had purchased non-prescription drugs from either a local pharmacy (83.4%, 61.4% medical & non-medical students respectively) or from seniors, friends & family members (18% medical & 18.8% non-medical students). The commonest indication for self-medication in both the groups was cough & cold (80.6% medical & 55.4% non-medical group) followed by fever in medical students (77.7%) and headache in non-medical students (39.6%). Antipyretics (66.9%) in medical students and analgesics (39.6%) in non-medical students were the commonest drug groups used. The medical students preferred to buy brand drugs (47.5%) as compared to generic drugs (26.6%) while the non-medical students had no preference (48.5%) about the form of drugs. About 57.6% medical and 61.4% non-medical students never experienced any side effect with over the counter drugs. Many medical (57.5%) and non-medical (40.6%) students supported the sale of non-prescription drugs for minor ailments. Conclusions: There is an increasing trend of self-medication among the youth today. Medical students have a better access to such drugs hence are expected to self-medicate more. But the easy availability about drug information on the internet and their unrestricted supply in the pharmacies are escalating the practice of self-medication among the general population too. It therefore becomes imperative to create awareness against the injudicious use of over the counter drugs without a valid medical prescription to promote rational drug use.